Coagulation profile after plasma exchange using albumin as a replacement solution measured by thromboelastometry. Issue 2 (18th September 2015) - Blasi, A.; Cid, J.; Beltran, J.; Taurà, P.; Balust, J.; Lozano, M.
Abstract : Background: Significant decrease in fibrinogen and other coagulation proteins is observed after plasma exchange when albumin is used as a replacement fluid. Little is known about how those changes impact on thromboelastometry (TEM). The aim of this study was to describe the changes in TEM after performing plasma exchange procedures using 5% albumin as a replacement fluid and its correlation with the standard coagulation tests. Study Design and Methods: Consecutive patients treated with plasma exchange were prospectively recorded. We performed laboratory and TEM assays extrinsec patway [EXTEM and fibrin‐based TEM (fibTEM)] from patient's blood sampled immediately before starting and immediately after finishing each procedure. Bleeding events during and after the procedure were monitored. Mann–Whitney U ‐test and Spearman's correlation test were used when needed. Results: After plasma exchange, all TEM parameters decreased under normal limits, especially the clotting time (CT): 62% reduction (range: 35–84%) and the fibTEM: 50% (range: 62–27%); maximum clot firmness (MCF) decreased to a lesser extent, 23% (range: 29–21%). Main TEM parameters showed a strong correlation with fibrinogen values: CT, r = −0·81; MCF, r = 0·85; and fibTEM, r = 0·79. No bleeding complications were observed. Conclusion: A profound derangement of TEM parameters was observed after PE, evidenced by delay in the clot formation and reduction in the clot firmness. More studies are warranted to elucidate the clinical implications of derangement in TEM parameters in patients without concomitant coagulopathy.